Ubiquity of particle–vortex interactions in turbulent counterflow of superfluid helium. (25th January 2021) - Švančara, P.; Duda, D.; Hrubcová, P.; Rotter, M.; Skrbek, L.; La Mantia, M.; Durozoy, E.; Diribarne, P.; Rousset, B.; Bourgoin, M.; Gibert, M.
Abstract: Abstract : Thermal counterflow of superfluid ^4 He is investigated experimentally, by employing the particle tracking velocimetry technique. A flat heater, located at the bottom of a vertical channel of square cross-section, is used to generate this unique type of thermally driven flow. Micronic solid particles, made in situ, probe this quantum flow and their time-dependent positions are collected by a digital camera, in a plane perpendicular to the heat source, away from the channel walls. The experiments are performed at relatively large heating powers, resulting in fluid velocities exceeding 10 mm s^-1, to ensure the existence of sufficiently dense tangles of quantized vortices. Within the investigated parameter range, we observe that the particles intermittently switch between two distinct motion regimes, along their trajectories, that is, a single particle can experience both regimes while travelling upward. The regimes can be loosely associated with fast particles, which are moving away from the heat source along almost straight tracks, and to slow particles, whose erratic upward motion can be said to be significantly influenced by quantized vortices. We propose a separation scheme to study the properties of these regimes and of the corresponding transients between them. We find that particles in both regimes display non-classical, broad distributions of velocity, which indicate the relevance of particle–vortex interactions in both cases. At the same time, we observe that the fast particles move along straighter trajectories than the slow ones, suggesting that the strength of particle–vortex interactions in the two regimes is notably different.